Security Price Response to Quarterly Earnings Announcements and Analysts' Forecast Revisions - Cornell, Bradford; Landsman, Wayne R. (The Accounting Review, 1989)
[The degree to which earnings changes are thought to be permanent may determine the magnitude of the security price response to a given earnings announcement [Brown et al., 1985; Kormendi and Lipe, 1987; and Easton and Zmijewski, 1987]. This study extends this literature by examining the impact on stock prices of quarter ahead and year ahead forecast revisions, as well as forecast errors. Results indicate that analysts' forecast revisions provide significant incremental explanatory power in a pooled time-series, cross-sectional regression of abnormal returns on forecast errors and analyst forecast revisions. In addition, the fourth quarter announcement appears to provide more information to analysts and investors than interim announcements.]